Salmonella infection ( Salmonella panama: 1,9,12: 1, v: 1,5 ) in swine ( Sus scrofa domesticus ) - Xavier, Vicente Leite; Langenegger, Charlotte Hubinger (Pesquisa Agropecuaria Brasileira, 2014)
A strain of Salmonella panama was isolated and identified from the liver, lungs, spleen and mesenteric lymph nodes of a five month old domestic pig (Sus scrofa domesticus), which died shortly after arrival at the. Instituto de Biologia Animal, IPEACS, Ministério da Agricultura. The case history and clinical symptoms of the pig prior to death were not available for diagnosis of cause of death. At necropsy, the following pathological conditions were observed: skin hemorrhages, oedematous and hemorrhagic lymphatic nodes, purulent bronchopneumonia with necrosis and calcification of the bronchial tubes, renal petechiae, rare ones on the urinary bladder, hemorrhages on the epiglottis, hemorrhagic infarcts on the spleen, and centrofollicular necrosis of the large intestine. Infestation of Trichuris sp. was also observed. Two "inocula", the first consisting of a "pooled" suspension of ground liver, spleen and lungs in physiological saline, and the second consisting of a suspension of ground mesenteric lymphnodes in physiological saline, were seeded on Bacto brilliant-green agar plates and, large quantities, were separately inoculated in Kauffmann-Mueller tetrathionate broth. A Salmonella strain was isolated from each media and identified by its morphological, motility, staining, cultural, bio-chemical characteristics and antigenic constitution (1,9, 12: 1, v: 1,5) as Salmonella panama. Due to the comparable types of lesions caused by salmonellosis and hog cholera and the lack of clinical symptoms available, the role of the Salmonella in the mortality of the pig was difficult to assess. Salmonella are constantly found as secondary invaders, complicating the deleterious action of the hog cholera virus. Some of the sera and the standard cultures (for absorption tests) used for the typing were kindly provided by the late Dr. Edwards (C.D.C. Atlanta, Ga.) and the others prepared at the former "Instituto de Biologia Animal", IPEACS. (Enteric Bacteriology Laboratory) with cultures from Edwards.